2020
DOI: 10.1071/cp19315
|View full text |Cite
|
Sign up to set email alerts
|

Tactical crop management for improved productivity in winter-dominant rainfall regions: a review

Abstract: This study reviews published information on the tactical management decisions needed to maximise economic grain yield in winter-dominant rainfall regions of the Mediterranean type. Tactical decisions are defined as those relating to the period from immediately before sowing to harvest. Tactical management is the principal means by which farmers respond to changing environmental and short-term economic conditions as the season progresses. The review considers published evidence that underpins these decisions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 182 publications
(230 reference statements)
0
4
0
2
Order By: Relevance
“…However, Kandulu et al (2012) suggested that, in many locations, a sole focus on diversification does not wholly mitigate the financial effects of climate variation. An alternative management method, applicable by farmers to manage their external variations, is to implement short-term tactical adjustments in response to unfolding conditions (Anderson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kandulu et al (2012) suggested that, in many locations, a sole focus on diversification does not wholly mitigate the financial effects of climate variation. An alternative management method, applicable by farmers to manage their external variations, is to implement short-term tactical adjustments in response to unfolding conditions (Anderson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Weeds are a major biotic constraint that can cause crop yield losses greater than those for other agricultural pests 1–3 . A continuous effort is required to keep weed infestation levels to a minimum as weeds are generally very prolific plants.…”
Section: Introductionmentioning
confidence: 99%
“…Weeds are a major biotic constraint that can cause crop yield losses greater than those for other agricultural pests. [1][2][3] A continuous effort is required to keep weed infestation levels to a minimum as weeds are generally very prolific plants. Since its inception, herbicide technology has been increasingly used by farmers worldwide as the most cost-effective weed control measure.…”
Section: Introductionmentioning
confidence: 99%
“…В останні десятиліття спостерігаються зміни клімату, так зване «глобальне потепління», внаслідок якого відбувається підвищення температурного режиму, частішають посушливі періоди та збільшується їх тривалість [35,36,38], що призводить до значних коливань урожайності сільськогосподарських культур як у просторі, так і в часі [1,16,32]. Підвищення температури в сільськогосподарських регіонах світу значно впливає на кількість опадів і їх перерозподіл протягом вегетаційного періоду, що призводить до значного зниження врожайності сільськогосподарських культур [6,28,37,39].…”
unclassified